2001
DOI: 10.1093/ndt/16.7.1382
|View full text |Cite
|
Sign up to set email alerts
|

Urinary albumin excretion rate and glomerular filtration rate in the prediction of diabetic nephropathy; a long‐term follow‐up study of childhood onset type‐1 diabetic patients

Abstract: At a mean diabetes duration of 29 years the cumulative incidence of macroalbuminuria was 12%; however, another 20% had persistent microalbuminuria. A screening value of 24-h AER >15 mg/min was a strong predictor, whereas increased GFR was a weaker but significant predictor for micro and macroalbuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 21 publications
5
53
1
4
Order By: Relevance
“…Glomerular hyperfiltration has been associated with various diseases including diabetes mellitus, polycystic kidney disease, secondary focal segmental glomerulosclerosis, obesity, sleep apnea, cancer and blood disorders [37]. In patients with diabetes, hyperfiltration was reported to be a significant risk factor for developing macro-or microalbuminuria [38]. In patients with pre-hypertension, subpopulations with hyperfiltration were supposed to be at increased risk for subsequent kidney damage [39].…”
Section: Discussionmentioning
confidence: 99%
“…Glomerular hyperfiltration has been associated with various diseases including diabetes mellitus, polycystic kidney disease, secondary focal segmental glomerulosclerosis, obesity, sleep apnea, cancer and blood disorders [37]. In patients with diabetes, hyperfiltration was reported to be a significant risk factor for developing macro-or microalbuminuria [38]. In patients with pre-hypertension, subpopulations with hyperfiltration were supposed to be at increased risk for subsequent kidney damage [39].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease was observed in the cohort with onset of diabetes between 1979 and 1984, that is, 10 to 15 years later than in our study. A Swedish population study completed in 1999 reported a cumulative incidence of macroalbuminuria of 12% after an average diabetes duration of 29 years [21].…”
Section: Discussionmentioning
confidence: 99%
“…In type 1 diabetes, the reported prevalence of hyperfiltration usually ranges from 40% to 60% [2,9,15]. However, the prevalence of hyperfiltration in other studies in type 1 diabetes has varied from as low as 13% [16] to as high as 67% [17].…”
Section: Prevalence Of Hyperfiltration In Type 1 Diabetesmentioning
confidence: 98%
“…However, hyperfiltration has been traditionally defined as GFR >2 standard deviations above the mean GFR in control participants. The threshold for hyperfiltration has ranged from 125 to 140 ml min −1 1.73 m −2 in various studies [9,11,12].…”
Section: Measurement Of Gfrmentioning
confidence: 99%
See 1 more Smart Citation